SHIFTING TO GIG LABOUR: PERCEPTIONS OF SUSTAINABILITY - Isabel Pereira Rodrigues (2022)
Digitalization is a global megatrend. Digital labour platforms allow companies to outsource work through an open call to a crowd of people and are the forefront of the “gig economy”, characterized by one-off tasks, without further commitments for the involved partners. Sustainability is another megatrend and controversial from the gig economy perspective. Non-standard gig arrangements bring higher time flexibility for the workers, allowing more individuals to integrate with the labour market. However, these digital employment relationships are associated with relatively weak labour market institutions and regulations, resulting in precarious jobs. Using data collected by semi-structured interviews, this paper explores the experience of Swiss workers who switched from a “standard-contract” employment position to occasional gig employment. This study finds evidence that the voluntary change towards a gig job may be associated with an improvement in perceived social sustainability, but a degradation of economic and environmental sustainability. The conclusion may be specific to the high development context where the study took place, Switzerland. However, if that is the case, a stronger policy message emerges - even in newer forms of employment, protective legal frameworks ensuring a basic safety net for individuals continue to be key for more sustainable labour arrangements.